Psychomotorische Leistungsfähigkeit und Laktat- sowie Adrenalin- und Noradrenalinschwelle bei Fußballspielern im Verlauf ansteigender Belastungsintensität - Chmura, J.; Nazar, K.; Kaciuba-Uscilko, H.; Pilis, W.; Aust, F.; Wisnik, P. (Österreichisches Journal für Sportmedizin, 2001)
The aim of this study was twofold: 1. to investigate changes of psychomotoric reaction time during exercise of increasing intensity until achievement of VO2max and 2. to determine if there is a correlation betwen the concentration threshold of lactic acid, adrenalin and noradrenalin in blood and psychomotoric reaction time.